The Tradition of Melekan Manten: Cultural Da'wah Strategy of Mudin in Overcoming Social Problem - Rozi, Syaikhu; Rohmad, Muhammad Ali; Saifuddin, Saifuddin (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2021)
This research is a results description conducted to describe the social problem at the Melekan Manten event and the role of Mudin in reducing the social problem at the Melekan Manten event through Khataman al-Qur'an. The research is carried out by going directly into the field to investigate phenomena that appear in the real-life context. The process is by constructing phenomena based on the obtained data and critical evaluation based on relevant theories so that the essence of events can be found to be compared to other data and with relevant theories so that their validity, robustness and suitability can be tested and concluded. The study results concluded that the social problem in the Melekan Manten event in Delik and Kedungmaling, Mojokerto, namely playing cards, betting dice and dominoes, and drinking alcoholic beverages until drunk. The role of Mudin in reducing the ill behavior of the society is to implement da'wah management through a cultural approach. The role carried out is the role of community leader and spiritual leader to invite the youth to make Khataman al-Qur'an tradition at every Melekan Manten event.